O uso da informática no ensino aprendizagem nas séries iniciais em uma escola no município de Castanhal/PA - OLIVEIRA, Maria Lúcia Franco de (2019)
This paper entitled "the use of computer science in teaching learning in the initial series in a school in the municipality of Castanhal", had the general objective to analyze the factors that motivate the use of computers in teaching learning in the initial grades in the school. Specific objectives seek to identify situations in which teachers use information technology; understand the impacts perceived by teachers and students and how they react to these situations through the use of ICT resources; and realize how much the use of information technology can add to their teaching practice and consequently the students' learning. For the data collection, 22 questionnaires containing 21 free questions and 2 open questions were delivered at the end. From this result a considerable number of respondents considered their performance good when dealing with technological resources; most of them have personal computers, but they use their own cell phone to access the Internet, select contents and elaborate activities. The images are the most researched content by the interviewees; they emphasized that to extend the use of ICT in the classroom is the operation of laboratories, maintenance of machines and equipment, continuing training course and acquisition of more PC, Datashow, sound box etc. We are still facing a great challenge; there is still much to be done for the use of these technologies in teaching learning considering that they are one of the fundamental aspects for integral education and knowledge enrichment.